Identification, Cloning and Characterization of Selected Full-Length Fragrance-Related Transcripts from Orchid (Vanda Mimi Palmer) - Chan, Wai Sun (2009)
Floral fragrance has important economical value in ornamental plants, crops and industries related to essential oils. However, the understanding of the molecular mechanisms underlying the biosynthesis of floral fragrance in monocotyledonous plants; in particular orchids, is still in its infancy. This study aimed to isolate and characterize fragrance-related genes from Vanda Mimi Palmer in order to enhance understanding of the molecular biology of fragrance in vandaceous orchid. Vanda Mimi Palmer is a tropical scented orchid with high economical value. In the effort to identify potential fragrance-related genes in Vanda Mimi Palmer, a floral cDNA library and a subtracted cDNA library were constructed. A total of 100 clones were selected from the cDNA library and their nucleotide sequences were determined, of which 83 clones showed homology to known amino acid sequences, comprising 6 contigs and 62 singletons, which were further assigned into 9 categories based on their functional roles. Two ESTs were identified as potential fragrance-related transcripts and they were 1-deoxy-Dxylulose 5-phosphate reductoisomerase (DXR) and lipoxygenase. From the Suppression Subtractive Hybridization (SSH) library, 107 clones were up-regulated in the full bloom flowers of Vanda Mimi Palmer where 33 clones (3 singletons and 30 contigs) showed similarities to known sequences in the public database and were classified based on their putative functional roles as secondary metabolism (97%) and hypothetical proteins (3%), and 32 of the clones were transcripts encoding fragrance-related transcripts. The fragrance-related transcripts code for sesquiterpene synthase, tyrosine decarboxylase and putative alcohol acyltransferase. However, only three ESTs were selected for fulllength gene isolation and characterization and they are putative alcohol acyltransferase (VMPAAT), sesquiterpene synthase (VMPSTS) and DXR (VMPDXR). Southern analyses showed that each of the isolated transcripts belongs to a large gene family, containing more than one copy in the Vanda Mimi Palmer genome. Real time RT-PCR indicated that VMPAAT and VMPSTS transcripts were expressed preferentially in floral tissues whereas VMPDXR was expressed differentially in different types of tissues (root, leaf, petal, sepal and column). All three clones showed higher transcript expressions in blooming and full bloom flowers compared to flower bud. VMPAAT and VMPDXR transcripts expressions showed no fluctuations whereas VMPSTS showed otherwise. In conclusion, the findings in this study have contributed to the GeneBank database resources for orchids and have opened some insights on molecular biology of fragrance in vandaceous orchids.